New knowledge on how wild introgression shapes the adaptive genome landscape of native populations. - CGIAR Research Program on Livestock (2020)
Journal article describing how historical introgression from wild relatives enhanced climatic adaptation and resistance to pneumonia in sheep. Understanding the genetic mechanisms of adaptation in indigenous livestock populations is important for designing breeding programs aimed at producing animals that need to perform under a future changed environment.